Talent management practices and other factors affecting employee performance in the public healthcare sector in poland: an empirical study using structural equation modelling - Wioletta Pomaranik; Magdalena Kludacz-Alessandri (BMC Health Services Research)
Abstract Background In the healthcare sector, the quality of medical services largely depends on the work of medical staff. Improving employee performance can impact the efficiency and productivity of a healthcare entity. Therefore, proper talent management practices are needed to achieve good outcomes. It is also worth answering what other factors affect this performance. The aim of the study was to investigate the impact of talent management practices and other factors on employee performance in the public healthcare sector. Methods Data was collected using a questionnaire method with a Likert scale. The study population consisted of 558 employees in the public Polish healthcare sector. The research instrument's structure, reliability, and validity were assessed using exploratory and confirmatory factor analysis. Descriptive analysis was used to analyze the structure of respondents, and a covariance-based structural equation modelling (CB-SEM) was used to test the model and verify hypotheses. Survey data were analyzed using SPSS v8 and AMOS v. 29 (Predictive Solution Poland). Results In the structural equation model, CFI = 0.997, GFI = 0.992, AGFI = 0.973, and RMSEA = 0.033, showing the model has a good fit. Significant relationships were found between job mobility and employee performance (β = 0.195, p < 0.001) between talent management practices and employee performance (β = 0.246, p < 0.001). This analysis also showed a positive, significant and strong relationship between age and employee performance (β = 0.230; ρ value < 0.001). Conclusions The structural equation model showed that talent management practices consisting of talent attraction, talent development, and talent evaluation had a significant and positive impact on medical staff performance. We also found that, in addition to these three talent management practices, such factors as job mobility, and age were significant predictors of employee performance. It is, therefore, important to create formal talent management processes that support personal development and appreciate the individual performance of employees.